From Zone and Subjects to Line and Territory: A Theoretical Reflection on the Mexican-Guatemalan Boundary Dispute (1821-1882) - Buska, Soili (Universidad de Costa Rica, 2011)
This essay will examine the process of boundary dispute and definition between Guatemala and Mexico after 1821. The disagreement and negotiations over limits between countries revealed the wide-reached interest in delineation of national territories, fundamental for the formation of independent nation-states. Several ideological and economic factors affected the dispute and the final boundary treaty between Guatemala and Mexico. An important ideological influence played the nineteenth-century romantic nationalism, which made the Creole elites to establish particular and unique national entities. Moreover, the worldwide drive to map the earth‘s surface by using tools of the modern cartographic science played an important role in the process of Mexican-Guatemalan boundary definition. The postcolonial expansion of agro-export economy in Central America, and especially the coffee boom starting in the Mexican southeastern and Guatemalan western borderlands from the second half of the nineteenth century onward became an economic stimulus for boundary definition process. This is the historical context, in which Mexican and Guatemalan elites were engaged in a long-running debate and negotiations over the common border.